Knockdown of PTOV1 and PIN1 exhibit common phenotypic anti-cancer effects in MDA-MB-231 cells - Karna, Shibendra Kumar Lal (PLoS One, 2019)
BACKGROUND: Earlier, we have identified PTOV1 as a novel interactome of PIN1 in PC-3 cells. This study aims to explore the functional similarity and the common role of both genes in breast cancer cell proliferation. METHODS: CTG, crystal violet assay, clonogenic assay, wound healing assay, cell cycle analysis, Hoechst staining and ROS measurement were performed to assess cell viability, colony forming potential, cell cycle arrest, nuclear condensation and ROS production after knocking down of PTOV1 and PIN1 by siRNAs in MDA-MB-231 and MCF-7 cells. CO-IP, qPCR and western blot were performedto study interaction, transcriptional and translational regulation of both genes. RESULTS: Knockdown of PTOV1 and PIN1 inhibited the cell proliferation, colony formation, migration, cell cycle, and induced nuclear condensation as well as ROS production. Interaction of PTOV1 and PIN1 was validated by Co-IP in MDA-MB-231 cells. Genes involved in cell proliferation, migration, cell cycle, and apoptosis were regulated by PIN1 and PTOV1. PTOV1 knockdown inhibited Bcl-2, Bcl-xL and inducedBAX, LC3 and Beclin-1expression. Overexpression of PIN1 increased the expression of PTOV1. Knockdown of both genes inhibited the expression of cyclin D1, c-Myc, and β-catenin. CONCLUSIONS: PTOV1 and PIN1 interact and exert oncogenic role in MDA-MB-231 cells by sharing the similar expression profile at transcriptional and translational level which can be a promising hub for therapeutic target.